Analisis Swot Sebagai Upaya Pengembangan dan Penguatan Strategi Menghadapi Persaingan : (Studi pada SMA IT Insan Mulia Boarding School Pringsewu) - M. Badrun; Edi Harapan; Rizal Ahmad (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This research aims to determine 1) the strengths and weaknesses faced by SMA IT Insan Mulia Boarding School Pringsewu Lampung, 2) the threats and opportunities faced by SMA IT Insan Mulia Boarding School Pringsewu Lampung, and 3) what alternative strategies can be taken in facing competition SMA IT Insan Mulia Boarding School Pringsewu Lampung which has excellence in the academic and non-academic fields with precise Islamic characteristics using the SWOT (Strength, Weakness, Opportunity, Threat) analysis method. This research uses a purely qualitative descriptive research design that describes what is or happens in the field. The research data source was obtained from interviews with school principals, teachers and other stakeholders. Data collection techniques use (1) interviews, (2) observation and (3) documentation. A SWOT analysis of SMA IT Insan Mulia Boarding School Pringsewu is very necessary to get a clear picture of internal analysis and external analysis in order to plan future school programs. The findings of this research are the results of internal analysis, the results of external SWOT analysis, and alternative strategies that can be taken in facing competition at SMA IT Insan Mulia Boarding School Pringsewu Lampung.